2016
DOI: 10.1016/j.rppede.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Maternal breastfeeding, early introduction of non-breast milk, and excess weight in preschoolers

Abstract: Objective:Investigate associations between excess weight in preschool children, breastfeeding duration and age of non-breast milk introduction.Methods:Cross-sectional study of a representative sample of 817 preschool children, aged 2-4 years, attending municipal day care centers in the city of Taubaté. The weight and height of children were measured in the day care centers in 2009, 2010 and 2011. The body mass index z-score (BMIz) was calculated and children were classified as risk of overweight (BMIz≥1 to<2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
0
2
0
5
Order By: Relevance
“…Maternal parity has also been associated with a lower risk of childhood overweight (26) , although this maybe dependent on breast-feeding (27) . Exclusive breast-feeding and later age of introduction of non-breast milk have shown protective effects on preschool overweight/obesity in some (28)(29)(30) but not all studies. Despite the well-established relationship between perinatal and early life factors with overweight and obesity at preschool years, their effect on BMI changes in this age group remains to be thoroughly investigated.…”
mentioning
confidence: 99%
“…Maternal parity has also been associated with a lower risk of childhood overweight (26) , although this maybe dependent on breast-feeding (27) . Exclusive breast-feeding and later age of introduction of non-breast milk have shown protective effects on preschool overweight/obesity in some (28)(29)(30) but not all studies. Despite the well-established relationship between perinatal and early life factors with overweight and obesity at preschool years, their effect on BMI changes in this age group remains to be thoroughly investigated.…”
mentioning
confidence: 99%
“…Grandmaternal influence on breastfeeding practices may have long‐term health consequences, as several studies have shown an association of shorter duration of breastfeeding with obesity, body fatness and the metabolic syndrome in childhood and adolescence (Ejlerskov et al, 2015 ; Grummer‐Strawn & Mei, 2004 ; Horta et al, 2013 ; Martorell et al, 2001 ; Nascimento et al, 2016 ; Wisnieski et al, 2018 ), though other studies find no such associations (Harder et al, 2005 ; Kramer et al, 2007 ; Sanchez‐Escobedo et al, 2020 ; Schwartz et al, 2015 ). Moreover, there is evidence that infant feeding mode may shape children's subsequent eating behaviors (Li et al, 2014 ; Mariscal Rizo et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pesquisas apontam que crianças que receberam alimentos antes do período adequado foram mais suscetíveis a doenças 7 , desnutrição 2 e obesidade 8 . Além dos prejuízos que são notados em curto prazo, de acordo com a OMS existem consequências em longo prazo, tais como, fraco desempenho escolar, produtividade diminuída e menor desenvolvimento intelectual e social 9 .…”
Section: Introductionunclassified